Position of Criminal Case Review Decision as Novum in Submission of Civil Case Review - Yunika S, Melisa (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to 1) find out and analyze whether a decision to review a criminal case can be used as new evidence (novum) on a review of a civil case. 2) To know and analyse how the criteria novum according to the Civil Procedure Law. Research method with the type of research in this research is normative law research (normative legal research). The type of research is a legal vacuum. The nature of research is prescriptive. The analysis of this research is done by criticising, supporting, or commenting, and then making a conclusion on the results of the research with the help of a library study. A method for normative research is a prescriptive method, a method of analysis that gives a judgment (justification) of the object being studied whether it is true or wrong or what it is supposed to be according to the law. Results of research obtained first; a novum must meet the requirement that the novum has to be definite, that it exists before the matter begins to be examined, and that it is not found when the process of examination is in progress. Second; Novum in civil matters is explicitly referred to as a means of proof of letters. Thus, the notion of evidence (novum) is evidence in the form of a letter containing a fact already existing at the time of a quo investigation in the first instance before the quo is settled by the court.